Four clinical phenotypes of cow’s milk protein allergy based on dairy product specific IgE antibody types in North China - Tang, Rui; Lyu, Xiaohong; Liu, Yi; Zhu, Mingzhi; Yang, Xukai; Wu, Zhoujie; Han, Bingnan; Wu, Shandong; Sun, Jinlyu (Frontiers in Immunology, 2022)
Background: Cow’s milk protein allergy (CMPA) is a common allergy. Immunoglobulin E (IgE)-mediated cow’s milk allergy is associated with a high mortality risk and poor prognosis. The study aims to investigate whether there are different clinically CMPA phenotypes in China and to explore the association between CMPA phenotypes and specific IgE (sIgE) antibodies against different dairy products. Methods: Serum sIgE against different animal milk and cow’s milk products and different milk components was measured by an allergen array. Four CMPA classifications were identified by the presence of serum sIgE: boiled milk-positive, yogurt-positive, buttermilk-positive, and raw milk-positive. Results: Of the 234 participants included in the study, 9 were boiled milk sIgE-positive, 50 were yogurt sIgE-positive, 17 were buttermilk sIgE-positive, and 158 were only raw milk sIgE-positive. The boiled milk-positive group had the highest levels of raw milk sIgE and casein sIgE antibodies, followed sequentially by the yogurt-positive, buttermilk-positive, and raw milk-positive groups. The highest levels of sIgE against raw milk, casein, α-lactalbumin and β-lactoglobulin were observed in the boiled milk group, and these levels differed significantly from those in the other three groups. Allergic symptoms were distributed differently among the four study groups. The percentages of allergic patients with gastrointestinal tract symptoms in the above mentioned four groups ranged from high to low, and the percentages of patients with skin symptoms in the four groups ranged from low to high, respectively. Conclusion: Based on dairy product sIgE antibody levels associated with different milk components and various clinical allergic symptom tendencies, we were able to distinguish four CMPA phenotypes.